Educating the Novice in Architecture through Collaborative Learning Approach - Abdorrahman Dinarvand; Hamid Nadimi; Ali Alai (صفه)
The present paper is aimed at improving architectural design education at foundation levels, which is of particular significance for architecture schools.  It focuses on collaborative learning method which, authors believe, is capable of fulfilling many educational objectives. As a learner-centred teaching method, collaborative learning is based on new constructivism theories.  The main focus here is on the question of ‘which collaborative teaching approach suits architecture foundation courses best’.To answer the question, a study of the governing principles of the learner-centred teaching method was conducted, followed by a critical review of the research findings on collaborative learning, and its applications in architecture education. In order to identify the educational objectives of architectural design foundation workshops, two sources were consulted:1- Course descriptions, from the curricula of the Iranian, as well as the world’s five top ranking architecture schools, given that course descriptions incorporate the visions of curriculum designers.2-  Practical and research achievements of design tutors in the architectural design foundation workshops, through their publications.The research method is descriptive and based on content analysis. The findings portray the main objectives of workshops as developing creativity in students, increasing their confidence, exploring their potentials, and also creating a constructive interaction with their tutors.  Bearing in mind the priority of training over mere teaching in foundation courses there is a need to adopt corresponding approaches and methods. This brings the research to the conclusion that collaborative learning approaches best suited for foundation courses particularly due to their stronger training potentials.